Lenticulostriate vasculopathy in newborns: whole genome sequencing data analysis - Dauengauer-Kirlienė, Svetlana; Pranauskas, Dovydas; Singh, Yogen; Kučinskas, Vaidutis; Urnikytė, Alina (Frontiers in Pediatrics, 2025)
ObjectivesLenticulostriate vasculopathy (LSV) refers to hyperechogenic vessels detected in thalami and basal ganglia, using cranial ultrasound. Awareness of LSV has revealed its links to various neonatal diseases that can affect brain development ante- or postnatally. Congenital infections and hypoxic- ischemic conditions are the main risk factors of LSV. However, precise etiology of LSV remains unknown. The aim of this study was to analyze the whole genome sequencing (WGS) data of newborns diagnosed with LSV to evaluate genetic linkages with LSV manifestation.Study designWe analyzed whole genome sequencing variation data of newborns with LSV (n = 6) and control group newborns (n = 19). WGS variation data was annotated using ANNOVAR in GRCh37 (hg19), RefSeqGene, gnomAD, SIFT, dbSNP151, CADD and gerp++gt2. Bash language was used to develop a program that counts variant frequency and compares them between groups.ResultsWe identified one exonic nonsynonymous variant putatively associated with LSV, located in WNK1 gene [NM_213655.5: c.2219T > C p.(Leu740Pro)]. This variant is associated with pseudohypoaldosteronism type 2C and hereditary sensory and autonomic neuropathy type 2A. Pseudohypoaldosteronism can increase blood pressure, resulting in damaged or stiff blood vessels, similar to LSV. The variant is currently classified as a variant of uncertain significance due to insufficient evidence to determine its definitive role in these conditions.ConclusionsThe identification of this unique variant in WNK1 provides a potential genetic link to the etiopathogenesis of LSV, offering new insights into this condition. However, further functional studies and more comprehensive genetic research are required to establish definitive associations.